(untitled) (The International Journal for Scientific Research, 2026)
This study assesses the spatial and structural empowerment of wheat production across Iraqi governorates in 2024 using the Positive Statistics Methodology, which emphasizes empowerment- and improvement-oriented measurement. A cross-sectional governorate-level dataset (n=15) was used, including harvested area (Area), yield (Yield), and total production (Prod). To enable spatial comparability, three positive indices were constructed: the Positive Empowerment Index (PEI), combining efficiency (yield) and capacity/scale (area) after Min–Max normalization; the Coverage Index (CI), capturing the attainment of three positive criteria (above the median) for area, yield, and production; and the Composite Positive Achievement Index (CPAI), computed as a weighted integration of PEI and CI. Governorates were then classified into three production levels (low/medium/high) using production tertiles. Kruskal–Wallis testing indicated statistically significant differences in CPAI across the three levels (H=10.640, df=2, p=0.005), with an increasing rank pattern favoring the high-production group. Post-hoc pairwise comparisons using Mann–Whitney with Bonferroni adjustment (α=0.0167) confirmed significant differences between low vs. high (p=0.009) and medium vs. high (p=0.016), while low vs. medium was not significant after correction (p=0.047). The findings indicate that positive achievement is not determined by production volume alone, but rather by a balanced profile of efficiency, scale, and multi-criteria attainment. The study recommends adopting CPAI as a planning-oriented benchmarking tool to compare governorates and prioritize targeted interventions based on explicit empowerment gaps in yield, area, or criterion coverage.